“I’ve not been knocked out, so I’ll probably be fine:” Amateur Rugby players do not know the risks they are taking - Daniel Walker; Adam Qureshi; David Marchant; Rebecca Murray; Alex Bahrami Balani (PLoS ONE, 2025)
Concussion is prevalent in British amateur Rugby and there is currently contradicting evidence of the attitudes and knowledge of concussion in Rugby players. As such this study aimed to investigate the reasons for the variance in attitudes and knowledge of concussion in British amateur Rugby. As concussion is a lived experience within sport, we utilised qualitative interviews using reflexive thematic analysis to assess data obtained from nine amateur Rugby players that had sustained over three concussions to understand if they are aware of the known risks associated with such injuries. Our findings show that poor duty of care from those around the player with suspected concussion was prevalent, and that this poor duty of care enables poor attitudes toward and limited knowledge of concussion. It was also discovered that a lack of education could explain this poor duty of care that is offered to Rugby players by non-players. Poor duty of care and lack of education encourage continued participation from the player with suspected concussion. When there are examples of World Rugby failing in their duty of care of the best players in the world, it is unsurprising that players and non-players in the amateur game follow suit. Therefore, the education of both players and non-players in amateur Rugby matches is paramount, as well as World Rugby improving their concussion practices, in tackling the poor attitudes and knowledge base that we see in the amateur Rugby game.